2017
DOI: 10.3892/or.2017.6148
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IGF1 by tumor-associated macrophages promotes the proliferation and migration of epithelial ovarian cancer cells

Abstract: Abstract. Ovarian cancer (OC), of which epithelial ovarian cancer (EOC) is the most common, is the deadliest gynecological tumor because of the difficulties in detection at early stages, and metastasis and chemoresistance at advanced stages. Tumor-associated macrophages (TAMs) differentiate through alternative pathways and play important roles in tumor growth and metastasis. However, the underlying mechanism remains unclear. Here, we established a mouse TAM model using bone marrow monocytes and conditioned med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
1
31
1
1
Order By: Relevance
“…Other factors, including EGF, IGF1, and CHI3L1, have been proposed to be involved in the migration-promoting function of macrophages [22][23][24] , but these mediators are not among the proteins upregulated in the pro-migratory MDM secretomes identified by our approach. Several reasons are likely to contribute to these differences.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Other factors, including EGF, IGF1, and CHI3L1, have been proposed to be involved in the migration-promoting function of macrophages [22][23][24] , but these mediators are not among the proteins upregulated in the pro-migratory MDM secretomes identified by our approach. Several reasons are likely to contribute to these differences.…”
Section: Discussionmentioning
confidence: 78%
“…For example, it is suggested that TAM and tumor cells cooperate in extracellular matrix (ECM) remodeling, which is a prerequisite for tumor cell adhesion and invasion 7,13,14 . Consistent with this model, it has been reported that TAM secrete migration-promoting factors like insulin-like growth factor 1 (IGF1), epidermal growth factor (EGF), and CHI3L1 pointing to a presumably central role of TAM in cancer cell migration, adhesion, and invasion [22][23][24] .…”
Section: Introductionmentioning
confidence: 64%
“…Further basic research manifested the IGF1 promoted the proliferation and migration of ovarian cancer cells and inhibition of IGF1 receptor and the downstream molecules effectively suppressed the malignant phenotype of tumor cells. Therefore, targeting the IGF1 pathway may be promising for the treatment for ovarian cancer patients with liver metastases(12). Joelle et al found that the cell surface glycoprotein CD44 contributed to the spheroid formation, mesothelial adhesion and mesenteric metastasis in epithelial ovarian carcinoma.…”
mentioning
confidence: 99%
“…However, our present study showed no significant decrease in the VEGF levels of the TAMs in the [14,15,41,42]. IGF-1 has been shown to signal intracellularly through the PI3 and MAPK pathways after binding to IGF-1R on the cell surface, and IGF-1 thereby increases the enzymatic activity of MMP-2 and MMP-9 and enhances the proliferation and migration of tumor cells [14,15,[43][44][45]. Noticeably, IGF-1 derived from polarized macrophages can maintain the M2-type activation profile in these 15 macrophages by activating the PI3-K and MAPK pathways [43,46].…”
Section: Discussionmentioning
confidence: 82%